An Analysis of Lesson Plans for Learning English in the Senior High School - Ni Luh Soma Antari (Journal for Lesson and Learning Studies, 2021)
Preparation of lesson plans for learning English is an important aspect that must be done, before carrying out aspects of teaching and learning, but not all teachers are able to do this. This study aims to analyze the problems carried out by English teachers in high school. This research is qualitative research. The subject in this study was an English teacher. Data on the steps of preparing the RPP for learning English through google classroom and the problems were collected through a questionnaire. Data was collected by giving two questionnaires to the English teacher. The data obtained were analyzed descriptively and qualitatively. The results showed that the steps taken in the preparation of Indonesian language learning lesson plans followed 5 aspects of the 2013 curriculum lesson plans, namely learning objectives, learning materials, learning activities, media, and learning resources, learning. There were 7 problems that were found when they compiled the lesson plans for learning English, including those that occurred in the aspects of learning objectives, learning activities, and learning. So, it can be said that the lesson plan for learning English can be used in the online learning process.